2017
DOI: 10.3389/fmicb.2017.00784
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Associated with the Reef Coral Mussismilia braziliensis's Momentum Boundary Layer over a Diel Cycle

Abstract: Corals display circadian physiological cycles, changing from autotrophy during the day to heterotrophy during the night. Such physiological transition offers distinct environments to the microbial community associated with corals: an oxygen-rich environment during daylight hours and an oxygen-depleted environment during the night. Most studies of coral reef microbes have been performed on samples taken during the day, representing a bias in the understanding of the composition and function of these communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 94 publications
2
30
0
Order By: Relevance
“…Despite the above findings, a few field-based investigations did not observe differences in the seawater microbial composition or function surrounding corals compared to seawater sampled further away from the reef substrate (e. g. Silveira et al 2017;Walsh et al 2017), demonstrating that there is still much to be learned about potential coral -microbial interactions and the significance of these interactions for pathogen/symbiont recruitment and benthic-pelagic coupling on coral reefs. For example, how do environmental differences between reef locations impact coral-microbial dynamics surrounding individual coral colonies?…”
Section: Near Coral Seawater Microbial Communities and Their Potentiamentioning
confidence: 95%
“…Despite the above findings, a few field-based investigations did not observe differences in the seawater microbial composition or function surrounding corals compared to seawater sampled further away from the reef substrate (e. g. Silveira et al 2017;Walsh et al 2017), demonstrating that there is still much to be learned about potential coral -microbial interactions and the significance of these interactions for pathogen/symbiont recruitment and benthic-pelagic coupling on coral reefs. For example, how do environmental differences between reef locations impact coral-microbial dynamics surrounding individual coral colonies?…”
Section: Near Coral Seawater Microbial Communities and Their Potentiamentioning
confidence: 95%
“…Ambient nutrient concentrations have been shown to impact the microbial communities of corals, with local variations from 5-11 imol L-in total nitrogen explaining up to 40% of the taxonomic dissimilarity among dominant genera in a community of the tropical stony coral Mussismilia braZiliensis on a single reef (Silveira et al, 2017). The rate data from the present study do display an apparent correlation with ambient DIN concentrations ( Figure 4.2), although a larger sample size and analysis of the same species across various sites would contribute to explaining this trend more rigorously.…”
Section: Other Variations Among Speciesmentioning
confidence: 99%
“…Despite collecting large volumes (10 liters) of seawater that may have integrated the microbial heterogeneity that exists at smaller scales, Tout et al () found enrichment of copiotrophic bacteria near the corals, as well as genes used for bacterial motility, chemotaxis, membrane transport, iron acquisition, and metabolism of aromatic compounds in addition to other pathways. In contrast, Silveira et al () did not detect any significant differences in the functional or taxonomic microbial composition between large (80 liters) volume samples of near‐coral seawater (CSW) collected surrounding patches of the coral Mussismilia braziliensis and the water column. A study by Walsh et al () detected differences in the microbial communities of seawater within 5 cm of reef macro‐organisms compared to seawater sampled 3 m off of the reef except for the coral M. braziliensis , similar to the study conducted by Silveira et al ().…”
mentioning
confidence: 92%
“…In contrast, Silveira et al () did not detect any significant differences in the functional or taxonomic microbial composition between large (80 liters) volume samples of near‐coral seawater (CSW) collected surrounding patches of the coral Mussismilia braziliensis and the water column. A study by Walsh et al () detected differences in the microbial communities of seawater within 5 cm of reef macro‐organisms compared to seawater sampled 3 m off of the reef except for the coral M. braziliensis , similar to the study conducted by Silveira et al (). Finally, a recent study used syringes (50 mL volume) to sample seawater 0, 5, and 50 cm away from individual colonies of Acropora and Platygyra spp.…”
mentioning
confidence: 92%
See 1 more Smart Citation